Genetic ablation of soluble tumor necrosis factor with preservation of membrane tumor necrosis factor is associated with neuroprotection after focal cerebral ischemia. Issue 9 (September 2016) - Madsen, Pernille M; Clausen, Bettina H; Degn, Matilda; Thyssen, Stine; Kristensen, Lotte K; Svensson, Martina; Ditzel, Nicholas; Finsen, Bente; Deierborg, Tomas; Brambilla, Roberta; Lambertsen, Kate L
Microglia respond to focal cerebral ischemia by increasing their production of the neuromodulatory cytokine tumor necrosis factor, which exists both as membrane-anchored tumor necrosis factor and as cleaved soluble tumor necrosis factor forms. We previously demonstrated that tumor necrosis factor knockout mice display increased lesion volume after focal cerebral ischemia, suggesting that tumor necrosis factor is neuroprotective in experimental stroke. Here, we extend our studies to show that mice with intact membrane-anchored tumor necrosis factor, but no soluble tumor necrosis factor, display reduced infarct volumes at one and five days after stroke. This was associated with improved functional outcome after experimental stroke. No changes were found in the mRNA levels of tumor necrosis factor and tumor necrosis factor-related genes (TNFR1, TNFR2, TACE), pro-inflammatory cytokines (IL-1β, IL-6) or chemokines (CXCL1, CXCL10, CCL2); however, protein expression of TNF, IL-1β, IL-6 and CXCL1 was reduced in membrane-anchored tumor necrosis factor Δ/Δ compared to membrane-anchored tumor necrosis factor wt/wt mice one day after experimental stroke. This was paralleled by reduced MHCII expression and a reduction in macrophage infiltration in the ipsilateral cortex of membrane-anchored tumor necrosis factor Δ/Δ mice. Collectively, these findings indicate that membrane-anchored tumor necrosis factor mediates the protective effects of tumor necrosis factor signaling in experimental stroke, and therapeutic strategies specifically targeting soluble tumor necrosis factor could be beneficial in clinical stroke therapy.